Faktor Penghambat UMKM dalam Menggunakan Teknologi Informasi di Kabupaten Tanah Datar - Febria Rahim; Muhammad Ibrahim Nasution; Mirawati Mirawati; Eltri Erpita; Yulhaniva Yulhaniva (Universitas Negeri Padang, 2023)
In the current era of revolution 4.0, the use of information technology is not new, but has become an obligation for every business owner, including MSMEs, both using technology for administrative management and marketing of the products offered. However, in Tanah Datar District, only about 3.6% of MSME owners have started using information technology in their businesses. This condition makes it important to pay attention to what inhibiting factors influence MSME owners in Tanah Datar Regency in using Information Technology. The results of the study concluded that the first obstacle that caused SMEs in Tanah Datar Regency to use Information Technology was that SMEs stuttered that the use of Information Technology was not needed in their business. Second, the lack of ability in the use or application of technology to support business development and the ability to apply MSME product standards is still limited, and third, the ability in business management, time management, and the quality of human resources (HR) is still limited.